2021
DOI: 10.3390/microorganisms10010057
|View full text |Cite
|
Sign up to set email alerts
|

Water Relations, Gas Exchange, Chlorophyll Fluorescence and Electrolyte Leakage of Ectomycorrhizal Pinus halepensis Seedlings in Response to Multi-Heavy Metal Stresses (Pb, Zn, Cd)

Abstract: The success of mine site restoration programs in arid and semi-arid areas poses a significant challenge and requires the use of high-quality seedlings capable of tolerating heavy metal stresses. The effect of ectomycorrhizal fungi on different physiological traits was investigated in Pinus halepensis seedlings grown in soil contaminated with heavy metals (Pb-Zn-Cd). Ectomycorrhizal (M) and non-ectomycorrhizal (NM) seedlings were subjected to heavy metals stress (C: contaminated, NC: control or non-contaminated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 84 publications
(141 reference statements)
0
11
0
Order By: Relevance
“…The negative effect of heat stress on the physiological activity of many tree species is well documented [ 48 ], indicating that such perturbations can either result in reduced tree growth and production [ 49 ] or increased tree mortality [ 50 ]. To date, there is a lot of evidence concerning the positive effect of ectomycorrhizal fungi on plants’ gas exchange when exposed to different stress factors, including water scarcity [ 51 ], heavy metals [ 52 ], and salinity [ 53 ]; however, little research has attempted to answer the question of how ectomycorrhizal fungi can alleviate the negative effect of heat stress on plants through the modulation of gas exchange parameters. Indeed, most studies have focused on the role of arbuscular mycorrhizal fungi in the physiological response of plants to heat-induced stress [ 54 , 55 , 56 ].…”
Section: Discussionmentioning
confidence: 99%
“…The negative effect of heat stress on the physiological activity of many tree species is well documented [ 48 ], indicating that such perturbations can either result in reduced tree growth and production [ 49 ] or increased tree mortality [ 50 ]. To date, there is a lot of evidence concerning the positive effect of ectomycorrhizal fungi on plants’ gas exchange when exposed to different stress factors, including water scarcity [ 51 ], heavy metals [ 52 ], and salinity [ 53 ]; however, little research has attempted to answer the question of how ectomycorrhizal fungi can alleviate the negative effect of heat stress on plants through the modulation of gas exchange parameters. Indeed, most studies have focused on the role of arbuscular mycorrhizal fungi in the physiological response of plants to heat-induced stress [ 54 , 55 , 56 ].…”
Section: Discussionmentioning
confidence: 99%
“…The increased leaf ELR reflected a disrupted plasma membrane permeability [ 45 ]. It was reported that heavy metal toxicity such as excessive Pb, Zn and Cd significantly increased the ELR in needles of Pinus halepensis [ 46 ]. Moreover, it was also identified that Cu-sensitive jute varieties had significantly higher ELR than the Cu-resistant ones [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…Pukacki Odasz-Albrigtsen et al, 2000;Alessio et al, 2002;Naidoo and Chirkoot, 2004;Matsushima et al, 2009;Fusaro et al, 2021Wang et al, 2019 Pinus pinea, Quercus ilex; Hibiscus sp. ; Avicennia marina; Betula pubescens, Pinus sylvestris and 5 shrub species; Morus alba Heavy metals Kitao et al, 1998;Pereira et al, 2000;Dezhban et al, 2015;Zhang et al, 2020;Hachani et al, 2021;Reyes et al, 2022 Robinia pseudoacacia; Pinus halepensis; Betula ermanii, Alnus hirsuta; 4 Citrus species/cultivars; Quercus ilex, Nerium oleander, Pittosporum tobira; Citrus grandis, Citrus sinensis…”
Section: Gaseous Air Pollutantsmentioning
confidence: 99%
“…On the other hand, the ChF method allowed to confirm the beneficial effect of ectomycorrhizal fungi on recovery from contamination stress (Pb, ZN and Cd) in Pinus halepensis Mill. ( Hachani et al., 2021 ). The research on soil pollution influence was conducted mostly on crop plants.…”
Section: Chlorophyll a Fluorescence Measurements I...mentioning
confidence: 99%